BAGAIMANA CARA MENGAMATI LUKISAN KARYA AFFANDI - Gamal Kartono (BAHAS, 2008)
Affandi is an important figure of Indonesia modern painting art. As a maestro of Indonesia painting arts he had never stopped painting so that in thousands of his paintings had been producted. Humanism as its created base was very consistent that he struggled to conduct the experiment continuously. It could be signaled from his work which showed several techniques and objects of painting, among other things were the painting which enclosed the sun object. The sun as the natural power, that it was believed constituted the life source. Painting which enclosed the sun motif, seemed since his work  titled:” Potret Diri dan Tujuh Matahari di India” (1950), until “Potret Diri tak Tercapai” (1987). Its question is why did he often paint the sun and what was the meaning ? To know the sun meaning it was conducted the research using the semiotic approach. The researcher’s interpretation was carried out by analysis of two semiotic approachs, namely Peirce semiotic (threechotomy: icon, index, symbol); and Barthes connotative semiotic. The data analysis process was started from the icon analysis, index, and symbol, finally completed by connotetive analysis. The research output indicated that its empathy to the subject which was felt as the painter reality, the sun symbol as if Affandi was ‘sun’ itself. The sun was created by the life signal symbol, on its reality whereas Affandi’s way to paint outdoor needed the sunlight so much. In the final period its expressiveness trip, Affandi did not show the emosive lines causing the feeling to quiver, but he had changed to be the reflection. Nature in his interpretation was the faced reality where the sun was as his life source. Along with increasing the age, then its sun seems to be increasingly redder and duller.   Keywords: Lukisan Affandi, Kajian Semiotik